Consumptive Lifestyle against Fashion Trends through Online Shopping among Students (Case Study of Economics Department Students, Bengkulu University) - Lupita Sari (Budapest International Research and Critics University, 2022)
This paper analyzes the phenomenon of consumptive lifestyles on fashion trends that occur among students through online shopping, researchers use the theory of the consumer society from Jean Paul Baudrillard, to see how the lifestyle of students who are addicted to online shopping so that they become consumptive in the field of fashion. Data collection in this study using a descriptive qualitative approach was used as a guide for analysis. The research data were obtained through observation and in-depth interviews with six student informants majoring in economics at Bengkulu University. Secondary data documentation in the form of documents or literature from journals, magazines, and newspapers related to research problems.